Attention-deficit/hyperactivity disorder: diagnostic contribution of a computerized assessment of visual attention (Archives of Clinical Psychiatry, 2007)
OBJECTIVE: To investigate if performances in a visual attention test could discriminate between children and adolescents with ADHD and normal subjects. METHODS: 102 children and adolescents diagnosed with ADHD according to DSM-IV were submitted to the Test of Visual Attention (TAVIS-III) and had their performance compared to 678 normal paired subjects who comprised a control comparison group. All of the subjects were sequentially recruited from one public and two private schools, following parents authorization. RESULTS: ROC curves analysis have shown that simultaneous impairment in hit reaction time of focused attention, omission errors in shifted attention and commission errors in sustained attention revealed high sensibility and specificity, with positive predictive value of 87.5%. The negative predictive value was of 99% when the aforementioned indexes occurred simultaneously within normal range. CONCLUSION: The Test of Visual Attention (TAVIS-III) was efficient to discriminate persons with ADHD and normal persons in this non clinical sample.